MEDU-28. ELIMINATING THE ROOT OF MEDULLOBLASTOMA BY TARGETING A VOLTAGE-GATED POTASSIUM CHANNEL. (23rd April 2019) - Fan, Jerry; Pusong, Ronwell; Morrissy, Sorana; Farooq, Hamza; Taylor, Michael; Huang, Xi
Abstract: Medulloblastoma (MB) is the most common pediatric brain tumor. Current treatment modalities are aggressive and highly toxic to the developing brain, and survivors are left with long term cognitive defects and reduced quality of life. Furthermore, intratumoral heterogeneity and the presence of MB-propagating cells (MPCs) presents a major obstacle in the effective treatment of MB. Rare, self-renewing MPCs sustain long-term tumor maintenance, resist chemotherapy, and are a likely source of disease relapse. Together, these therapeutic challenges underscore the need for novel molecular targets which can eradicate MPCs while sparing the normal developing brain. We identified that the voltage-gated potassium channel KCNB2 is overexpressed in MB. Strikingly, while Kcnb2 is dispensable for normal murine development, loss of Kcnb2 markedly improves survival in genetic MB mouse models. Interestingly, Kcnb2 is enriched in MPCs. Loss of Kcnb2 significantly depletes the MPC population in part through increased differentiation. Prior to our studies, the role of ion channels in tumor-propagating cells was unknown. Our results suggest that the potassium channel KCNB2 plays a crucial role in the self-renewal and maintenance of MPCs, and that anti-KCNB2 therapies may be leveraged to eliminate MPCs and abrogate MB growth. The current study aims to elucidate the cellular and molecular mechanisms through which KCNB2 regulates MB growth.